Multiscale Climate Forcings Drive the Record Cold Spells in the Southwestern Atlantic Shelf During Falls 2016 and 2024 - Romina Trinchin; Marcelo Barreiro; Gastón Manta; Alberto R. Piola (International Journal of Climatology, 2026)
Cold sea surface temperature (SST) extremes, known as marine cold spells (MCS), have received less attention than marine heatwaves, particularly at the regional scale. This study examines the origin and drivers of autumn cooling events over the southwestern South Atlantic shelf (SWAS; 32° S–38° S), focusing on two record‐breaking cases in 2016 and 2024. We use ERA5 reanalysis, NOAA OI SST V2.1, and SMAP satellite products for SST and salinity, along with indices for the El Niño–Southern Oscillation (ENSO) and Madden–Julian Oscillation (MJO). These years presented negative SST anomalies in the Río de la Plata estuary and adjacent areas that were the most intense in the 43‐year long satellite record. The events were linked to exceptional river discharge (> 95th percentile) and anomalous surface southerly winds associated with a strong geopotential height dipole over southern South America at upper atmospheric levels. Results suggest these events arose from the interplay of several phenomena acting across different time scales: ENSO, MJO and climate change. El Niño increased rainfall over southeast South America and, by long‐term warming, the Indian Ocean favoured persistent MJO Phases 2 and 3, which reinforced atmospheric conditions sustaining the southerly winds over the SWAS. These winds drove surface heat loss and northward transport of colder, fresher waters from the Río de la Plata. Understanding these compound drivers improves MCS predictability, providing key insights for marine adaptation and management under climate change.

Northward intermittent pulses of Antarctic Intermediate Water beyond the Brazil/Malvinas Confluence - Michèle Baqués; Giuliana Berden; Marcela Charo; Paola M. Dávila; Alberto R. Piola (Progress in Oceanography, 2026)

Effects of regional oceanography and climate variability on larval connectivity of the wedge clam Donax hanleyanus in South American beaches - Erika Meerhoff; Vincent Combes; Ricardo Matano; Nicolas Barrier; Barbara C. Franco; Alberto R. Piola; Freddy Hernández-Vaca; Omar Defeo (Estuarine, Coastal and Shelf Science, 2025)

Facing oceanographic, fisheries, and governance hotspots: Scientific evidence and policy implications from the southwest South Atlantic Ocean - Omar Defeo; Bárbara C. Franco; Alberto R. Piola; Claudio C. Buratti; Luis Gustavo Cardoso; Federico Cortés; Ignacio Gianelli; Micaela Giorgini; Gabriela Jorge-Romero; Diego Lercari; Erika Meerhoff; Leonardo Ortega; et al. (Marine Policy, 2025)

Editorial: Sea ice - ocean interactions - David Docquier; Leandro Ponsoni; Amélie Simon; Alberto R. Piola (Frontiers in Marine Science, 2023)

Convergence of the Malvinas Current branches near 44°S - Dmitry I. Frey; Alberto R. Piola; Eugene G. Morozov (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

Shelf Water Export at the Brazil-Malvinas Confluence Evidenced From Combined in situ and Satellite Observations - Gaston Manta; Sabrina Speich; Marcelo Barreiro; Romina Trinchin; Camila de Mello; Rémi Laxenaire; Alberto R. Piola (Frontiers in Marine Science, 2022)
The Brazil-Malvinas Confluence (BMC) is the region where opposing and intense western boundary currents meet along the Southwestern Atlantic slope at about 38°S, generating one of the most energetic mesoscale regions of the global ocean. Based on shipborne observations acquired within the Uruguayan Economic Exclusive Zone (EEZ), combined with satellite data and an eddy tracking algorithm, we analyze the cross-shelf exchanges during May 2016, when the BMC was in an anomalous northern position. Two types of shelf water export were observed triggered by mesoscale dynamics: one was the export of shallow Rio de la Plata Plume waters driven off-shelf by the retroflection of the Brazil Current. This export formed a 70 km wide, 20 m deep filament that propagated offshore at 0.3 m s –1 , with a transport of 0.42 Sv. It lasted about 10 days before being mixed with ambient Confluence waters by strong winds. An additional type of off-shelf transport consisted of a subsurface layer of Subantarctic Shelf Waters (SASW) about 60 m thick that subducted at the BMC reaching 130 m deep and transporting 0.91 ± 0.91 Sv. We show that geostrophic currents derived from satellite altimetry over the slope can be useful to track this subsurface off-shelf export as they are significantly correlated with absolute velocity measurements at this depth. Argo temperature and salinity profiles show evidence of these two types of shelf water export occurring between the BMC front and the separation of the Brazil Current from the shelf-break, suggesting this is a relatively frequent phenomenon, in agreement with previous observations.

Cross-Shelf Exchange in the Southwestern Atlantic Shelf: Climatology and Extreme Events - Giuliana Berden; Alberto R. Piola; Elbio D. Palma (Frontiers in Marine Science, 2022)
The variability and drivers of the cross-shelf exchanges between the Southwestern Atlantic shelf and the open ocean from 30 to 40°S are analyzed using a high-resolution ocean model reanalysis at daily resolution. The model's performance was first evaluated using altimetry data, and independent mooring and hydrographic data collected in the study area. Model transports are in overall good agreement with all other estimates. The record-mean (1993–2018) cross-shore transport is offshore, 2.09 ± 1.60 Sv. 73% of the shelf-open ocean exchange occurs in the vicinity of Brazil-Malvinas Confluence (~38°S) and 20% near 32°S. This outflow is mostly contributed by northward alongshore transport through 40°S (63%) and the remaining by southward transport through 30°S (37%). The cross-shore flow presents weak seasonal variations, with a maximum in austral summer, and high variability at subannual and weekly time scales. The latter is mainly associated with abrupt wind changes generated by synoptic atmospheric systems. Alongshore wind variations set up sea-level changes in the inner shelf which in turn drive large anomalies in the associated geostrophic alongshore flow. The difference in inner shelf sea-level anomalies at 30 and 40°S is a good indicator of cross-shelf exchange at seasonal and shorter time scales. Episodes of extreme offshore transport that reach up to 9.45 Sv and last about 2 days are driven by convergence of these alongshore flows over the shelf. Large exports of shelf waters lead to freshening of the upper open ocean as revealed by in-situ and satellite observations. In contrast, onshore extreme events drive open ocean water intrusions of up to 6.53 Sv and last <4 days. These inflows, particularly the subtropical waters from the Brazil Current, induce a substantial salinification of the outer shelf.

Interannual Variability and Trends of Sea Surface Temperature Around Southern South America - Daniela B. Risaro; María Paz Chidichimo; Alberto R. Piola (Frontiers in Marine Science, 2022)
The interannual variability and trends of sea surface temperature (SST) around southern South America are studied from 1982 to 2017 using monthly values of the Optimally Interpolation SST version 2 gridded database. Mid-latitude (30°–50°S) regions in the eastern South Pacific and western South Atlantic present moderate to intense warming (~0.4°C decade −1 ), while south of 50°S the region around southern South America presents moderate cooling (~ −0.3°C decade −1 ). Two areas of statistically significant trends of SST anomalies (SSTa) with opposite sign are found on the Patagonian Shelf over the southwest South Atlantic: a warming area delimited between 42 and 45°S (Northern Patagonian Shelf; NPS), and a cooling area between 49 and 52°S (Southern Patagonian Shelf; SPS). Between 1982 and 2017 the warming rate has been 0.15 ± 0.01°C decade −1 representing an increase of 0.52°C at NPS, and the cooling rate has been –0.12 ± 0.01°C decade −1 representing a decrease of 0.42°C at SPS. On both regions, the largest trends are observed during 2008–2017 (0.35 ± 0.02°C decade −1 at NPS and –0.27 ± 0.03°C decade −1 at SPS), while the trends in 1982–2007 are non-significant, indicating the record-length SSTa trends are mostly associated with the variability observed during the past 10 years of the record. The spectra of the records present significant variance at interannual time scales, centered at about 80 months (~6 years). The observed variability of SSTa is studied in connection with atmospheric forcing (zonal and meridional wind components, wind speed, wind stress curl and surface heat fluxes). During 1982–2007, the local meridional wind explains 25–30% of the total variance at NPS and SPS on interannual time scales. During 2008–2017, the SSTa at NPS is significantly anticorrelated with the local zonal wind ( r = –0.85), while at SPS it is significantly anticorrelated with the meridional wind ( r = –0.61). Our results show that a substantial fraction of the interannual variability of SSTa around southern South America can be described by the first three empirical orthogonal function (EOF) modes which explain 28, 16, and 12% of the variance, respectively. The variability of the three EOF principal components time series is associated with the combined variability of El Niño–Southern Oscillation, the Interdecadal Pacific Oscillation and the Southern Annular Mode.

Climate change impacts on the atmospheric circulation, ocean, and fisheries in the southwest South Atlantic Ocean: a review - Bárbara C. Franco; Omar Defeo; Alberto R. Piola; Marcelo Barreiro; Hu Yang; Leonardo Ortega; Ignacio Gianelli; Jorge P. Castello; Carolina Vera; Claudio Buratti; Marcelo Pájaro; Luciano P. Pezzi; et al. (Climatic Change, 2020)

Dynamical connections between large marine ecosystems of austral South America based on numerical simulations - Karen Guihou; Alberto R. Piola; Elbio D. Palma; Maria Paz Chidichimo (Ocean Science, 2020)
The Humboldt Large Marine Ecosystem (HLME) and Patagonian Large Marine Ecosystem (PLME) are the two largest marine ecosystems in the Southern Hemisphere and are respectively located along the Pacific and Atlantic coasts of southern South America. This work investigates the exchange between these two LMEs and its seasonal and interannual variability by employing numerical model results and offline particle-tracking algorithms. Our analysis suggests a general poleward transport on the southern region of the HLME, a well-defined flux from the Pacific to the Atlantic, and equatorward transport on the PLME. Lagrangian simulations show that the majority of the southern PS waters originate from the upper layer in the southeast South Pacific (

Linking the scientific knowledge on marine frontal systems with ecosystem services - Paulina Martinetto; Daniela Alemany; Florencia Botto; Matías Mastrángelo; Valeria Falabella; E. Marcelo Acha; Gustavo Antón; Alejandro Bianchi; Claudio Campagna; Guillermo Cañete; Pablo Filippo; Oscar Iribarne; et al. (Ambio, 2020)

Global Perspectives on Observing Ocean Boundary Current Systems - Robert E. Todd; Francisco P. Chavez; Sophie Clayton; Sophie Cravatte; Marlos Goes; Michelle Graco; Xiaopei Lin; Janet Sprintall; Nathalie V. Zilberman; Matthew Archer; Javier Arístegui; Magdalena Balmaseda; et al. (Frontiers in Marine Science, 2019)

Variability and 20-Year Trends in Satellite-Derived Surface Chlorophyll Concentrations in Large Marine Ecosystems around South and Western Central America - Marina Marrari; Alberto R. Piola; Daniel Valla (Frontiers in Marine Science, 2017)

Characteristics and causes of Deep Western Boundary Current transport variability at 34.5° S during 2009–2014 - Christopher S. Meinen; Silvia L. Garzoli; Renellys C. Perez; Edmo Campos; Alberto R. Piola; Maria Paz Chidichimo; Shenfu Dong; Olga T. Sato (Ocean Science, 2017)
The Deep Western Boundary Current (DWBC) at 34.5° S in the South Atlantic carries a significant fraction of the cold deep limb of the Meridional Overturning Circulation (MOC), and therefore its variability affects the meridional heat transport and consequently the regional and global climate. Nearly 6 years of observations from a line of pressure-equipped inverted echo sounders (PIESs) have yielded an unprecedented data set for studying the characteristics of the time-varying DWBC volume transport at 34.5° S. Furthermore, the horizontal resolution of the observing array was greatly improved in December 2012 with the addition of two current-and-pressure-equipped inverted echo sounders (CPIESs) at the midpoints of the two westernmost pairs of PIES moorings. Regular hydrographic sections along the PIES/CPIES line confirm the presence of recently ventilated North Atlantic Deep Water carried by the DWBC. The time-mean absolute geostrophic transport integrated within the DWBC layer, defined between 800–4800 dbar and within longitude bounds of 51.5 to 44.5° W, is −15 Sv (1 Sv = 106 m3 s−1; negative indicates southward flow). The observed peak-to-peak range in volume transport using these integration limits is from −89 to +50 Sv, and the temporal standard deviation is 23 Sv. Testing different vertical integration limits based on time-mean water-mass property levels yields small changes to these values, but no significant alteration to the character of the transport time series. The time-mean southward DWBC flow at this latitude is confined west of 49.5° W, with recirculations dominating the flow further offshore. As with other latitudes where the DWBC has been observed for multiple years, the time variability greatly exceeds the time mean, suggesting the presence of strong coherent vortices and/or Rossby Wave-like signals propagating to the boundary from the interior.

Erosional and depositional contourite features at the transition between the western Scotia Sea and southern South Atlantic Ocean: links with regional water-mass circulation since the Middle Miocene - Lara F. Pérez; F. Javier Hernández-Molina; Federico D. Esteban; Alejandro Tassone; Alberto R. Piola; Andrés Maldonado; Benedict Preu; Roberto A. Violante; Emanuele Lodolo (Geo-Marine Letters, 2015)

Methods for estimating the velocities of the Brazil Current in the pre-salt reservoir area off southeast Brazil (23∘ S–26∘ S) - Tiago Carrilho Biló; Ilson Carlos Almeida da Silveira; Wellington Ceccopieri Belo; Belmiro Mendes de Castro; Alberto Ricardo Piola (Ocean Dynamics, 2014)